Penggunaan Model PJBL Pada Implementasi P5 Tema Berkebhinekaan Global Siswa Kelas 4 - Ainiyah, Rohmatul; Rifayanti, Zuni Eka Tiyas (Prodi Pendidikan Guru Sekolah Dasar, 2024)
This research describes the implementation process of the Project Based Learning (PJBL) model in the Pancasila Student Profile Strengthening Project (P5) with the theme of Global Diversity for 4th-grade students at SDU AL-HIKMAH Pakal, Surabaya. This study aims to describe the implementation of the PJBL model in the P5 theme of Global Diversity and to describe the implementation of the P5 theme of Global Diversity for 4th-grade students at SDU AL-HIKMAH. The research method used is qualitative descriptive. The research results show that the implementation of PJBL in the P5 material involves several stages, starting from project planning, project execution, to evaluation. The challenges faced in the implementation of the P5 project on the theme of global diversity include differences in students' abilities and project tools/materials being left at home. To overcome these obstacles, teachers need to make various efforts such as providing intensive guidance to students who do not understand well and involving parents.